EP939 Neoadjuvant chemotherapy (NAC) for patients with carcinomatosa peritonitis improves prognosis of those patients. (1st November 2019) - Nishimura, M; Kagawa, T; Mineda, A; Abe, A
Abstract : Introduction/Background: For patients with carcinomatosa peritonitis who are diagnosed to be difficult to completely remove in the first surgery, our hospital is performing tumor reduction surgery after neoadjuvant chemotherapy (NAC). Methodology: NAC has performed 4–5 courses of dose dense TC, and when it is judged that complete removal is possible, interval debulking surgery (IDS) is performed. Of the 39 cases of advanced ovarian cancer (stage III/IV) whose treatment was started in 2013–2018, 17 cases underwent surgery (PDS) and 22 cases underwent NAC for first treatment. The 22 cases consisted of 2 cases of test laparotomy, 2 cases of partial resection at the first surgery (PDS) and 18 cases of NAC. Results: Seventeen of the 18 NAC cases were diagnised by needle biopsy. The response rate for NAC was 94% (17/18). The complete resection rate at IDS was 72% (13/18). Recurrence was observed in 46% (6/13) of the cases achieving complete resection and 80% (4/5) in the remaining cases. The response rate of subsequent chemotherapy was 100% (5/5) in 5 patients with large residual tumors with PDS, and no recurrence was found in 3 patients who could be completely resected with subsequent IDS. The 5-year survival rate was 92% in the PDS group and 48% in the NAC and IDS group. The survival rate of patients with completely resection was 90%, and that of the remaining tumor was 18%. In addition, even in the case of patients with carcinomatosa peritonitis, 5 year survival rate was 85% in cases where there was no residual tumor at IDS. Conclusion: The prognosis was extremely good if complete resection with NAC and IDS was possible even in cases where complete resection was difficult in the first surgery. There were no surgical complications or deaths. NAC is considered a very effective treatment for carcinomatosa peritonitis cases. Disclosure: Nothing to disclose.